Electric propeller drive based on a reactive electric machine for ice-class ships - F. A. Gelver; I.V. Belousov; V.F. Samoseiko; A.V. Saushev (Российская Арктика)
The article presents the results of theoretical and experimental studies of a propulsion electric drive based on reactive electric machines with anisotropic magnetic conductivity of the rotor of a wide power range from 1.5 kW to 1.7 MW. The designs of various versions and types of rotors of such electric machines are described, their advantages and disadvantages are presented. It is shown that reactive electric machines have a simple design, high reliability and, in terms of a number of operational characteristics, safety, and manufacturing technology, especially for high-power electric machines, surpass all known types of electric machines. A mathematical description of a reactive electric machine with anisotropic magnetic conductivity of the rotor is given and its structural diagram in the rotor coordinate axes d, q is compiled. An algorithm for robust control of a propulsion electric drive is synthesized for ice-class vessels, providing for adjustment of the magnetization current and load current regulators by the method of sequential correction to the technical optimum. The synthesis of the electric drive control system is performed for two criteria: maximum speed and the highest energy efficiency index. The results of testing the developed design theory and control theory of reactive electric machines in a propulsion electric drive are presented. The theoretical and experimental studies have proven the adequacy of the developed design methodology. The prospects of application and wide capabilities of a propulsion electric drive based on reactive electric machines with anisotropic magnetic conductivity of the rotor for ice-class vessels are shown and proven.in the subjects during descents in diving сlosed circuit diving rebreathers with electronic control increased slightly and did not lead to the onset of symptoms of acute decompression sickness. This study remains relevant for working diving descents in open water, since the proposed methods make it possible to assess intravascular gas formation directly at the site of diving operations.